GC-MS Analysis and In Silico Molecular Docking Study of Caulerpa racemosa Microcapsules Under Heat Exposure - Dewi, Eko Nurcahya; Purnamayati, Lukita; Yuliani, Yuliani; Matanjun, Patricia (Marine Science Department Diponegoro University, 2025)
Caulerpa racemosa is a nutritionally rich green seaweed with bioactive properties, but its components are sensitive to high temperatures. The application of microencapsulation protects its bioactive compounds during exposure to high temperatures, which can otherwise cause degradation. This study aims to investigate the primary bioactive components in C. racemosa microcapsules subjected to high temperatures (120°C, 140°C, and 160°C) for 5 h. The phytoconstituents were identified using GC-MS. Additionally, an in-silico analysis, including ADME profiling and molecular docking, was conducted using BIOVIA Discovery Studio to assess the pharmacokinetic properties and potential biological interactions of the identified compounds. GC-MS analysis revealed that microcapsules treated at 120°C contained propane 2,2-diethoxy, while at 140°C, two additional compounds, furfural, and 2-furancarboxaldehyde, 5-methyl-, were identified. However, no active compounds were detected in microcapsules treated at 160 °C. Volatile compounds from the alcohol, aldehyde, furan, and ester groups increased with higher temperatures, particularly aldehydes and furans between 120°C and 140°C. The PASS database highlighted the potential of C. racemosa microcapsules in the development of safe, next-generation drugs, that adhere to ADMET properties. Molecular docking studies were performed with NF-κB and MMP-9 receptors. Among the tested compounds, 2-furancarboxaldehyde, 5-methyl- demonstrated the highest affinity for macromolecular targets. This compound's amine group showed strong binding to MMP-9 at Val A:398, suggesting its potential as an antioxidant and anti-inflammatory agent to mitigate illness.